LEGAL ANALYSIS OF LEGAL PROTECTION FOR CONSUMERS IN FINANCING AGREEMENTS WITH FIDUCIARY GUARANTEES IN THE DIGITAL AGE (RESEARCH STUDY IN THE CITY OF BATAM) - Aris Munandar; Soerya Respationo; Erniyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Land issues in Batam City have become an important issue due to the development of digital technology, which has driven changes in the mechanism of financing agreements with fiduciary guarantees, from conventional systems to electronic systems through Fidusia Online services. This situation has legal implications, particularly in relation to legal protection for consumers who are faced with standard clauses, the risk of misuse of personal data, and unilateral enforcement practices by creditors. This study aims to analyze the legal regulations regarding the role of notaries in ensuring the validity of digital fiduciary agreements, examine the implementation of the role of notaries in protecting consumer rights, and identify obstacles and formulate solutions in the implementation of legal protection in Batam City. The research method used is normative legal with a regulatory approach to examine regulations related to digital fiduciary, as well as empirical legal through interviews and observations with notaries and consumers in Batam City to obtain primary data. The theories used include the theory of justice as a grand theory, consumer protection theory as a middle theory, and legal effectiveness theory as an applied theory. The results of the study show that normatively, the legal basis for digital fiduciary agreements is found in the Fiduciary Guarantee Law, the ITE Law, the Consumer Protection Law, and the Minister of Law and Human Rights Regulation on Online Fiduciary, although there are still gaps in regulations related to digital deeds and electronic signatures. Empirically, notaries play an active role in explaining the contents of agreements, supervising the obligations of creditors, and protecting consumer rights. However, the effectiveness of legal protection is still hampered by limitations in digital infrastructure, low consumer legal literacy, and arbitrary enforcement practices by creditors. The recommendations include harmonizing digital fiduciary regulations with consumer protection, strengthening the role of notaries in providing digital legal advice, improving infrastructure and technology training, supervising digital contracts by the OJK and the Ministry of Law and Human Rights, and increasing legal education for the public so that they better understand their rights and obligations.